ANALYSIS OF MISCONCEPTION TO SCIENCE LITERACY USING THREE TIER MULTIPLE CHOICE TEST IN THE MATERIALS OF CHARACTERISTIC OF LIGHT - Wahyuningsih, Sri; Rusilowati, Ani; Hindarto, Nathan (Unnes Science Education Journal, 2017)
Mastery of science literacy is the main focus of education. A factor influencing low science literacy of Indonesian students is a misconception. Recently, research on diagnostic test development regarding misconception of science literacy is very limited. Actually, there should be a correction to the learning system. Initial observation of Science class in SMP Negeri 05 Semarang showed that students had difficulty in understanding the materials of light. The evaluation tool used by the teacher was not used to show the misconception of science literacy. In this case, this research was done to develop three-tier multiple-choice (3TMC) test with science literacy aspect to unveil students’ misconception of science literacy in the materials of characteristics of lights. The samples of this research were VIIIE and VIIIF using mix method with sequential explanatory strategy. The result showed that the instruments of 3TMC test with the aspect of science literacy produced 30 test items with 25 items which fulfill the criteria of valid, reliable, enough distraction level, and tolerable difficulty level. Meanwhile, the other 5 items did not fulfill the criteria. The result of interpretation showed that commonly, students had a misconception of science literacy terms of understanding (A), the competence of science investigation (B), science as the way of thinking (C), and the application of science to technology, society, and environment. The deep interview was done to 7 students who had the highest score of misconception of science literacy. They got the misconception to the indicators of characteristics of light, a process of vision, eye defects, and optical devices.